2018
DOI: 10.48550/arxiv.1803.00958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A study in $\mathbb{G}_{\mathbb{R}, \geq 0}$: from the geometric case book of Wilson loop diagrams and SYM $N=4$

Abstract: We study the geometry underlying the Wilson loop diagram approach to calculating scattering amplitudes in the gauge theory of Supersymmetric Yang Mills (SYM) N = 4. By applying the tools developed to study total positivity in the real Grassmannian, we are able to systematically compute with all Wilson loop diagrams of a given size and find unexpected patterns and relationships between them. We focus on the smallest nontrivial multi-propagator case, consisting of 2 propagators on 6 vertices, and compute the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(42 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…However the WLDs apparently lend themselves very naturally and directly to a geometrical interpretation and in this paper we wish to look again at the relationship between WLDs and the amplituhedron. Previous work also examining this connection includes [9,18,26]. In particular in [26] it was shown that the WLDs give a very natural description of the physical boundary of the amplituhedron.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However the WLDs apparently lend themselves very naturally and directly to a geometrical interpretation and in this paper we wish to look again at the relationship between WLDs and the amplituhedron. Previous work also examining this connection includes [9,18,26]. In particular in [26] it was shown that the WLDs give a very natural description of the physical boundary of the amplituhedron.…”
Section: Introductionmentioning
confidence: 98%
“…Previous work also examining this connection includes [9,18,26]. In particular in [26] it was shown that the WLDs give a very natural description of the physical boundary of the amplituhedron. Specifically here we wish to examine whether it is possible to use WLDs to define a tessellation of the amplituhedron or more generally a tessellation of any "good" geometrical shape, whereby "good" means it only has a physical boundary (corresponding to poles of the amplitude) without any spurious boundaries.…”
Section: Introductionmentioning
confidence: 98%
“…(3) After performing step (2) The squares which should contain a + label are specified by Algorithm 2: Placing + labels in these squares and 0 labels in all remaining squares, we obtain the Le diagram The reader is invited to verify that applying Algorithm 1 to L(I) above yields exactly the Grassmann necklace in (A).…”
Section: Reversing Oh's Algorithmmentioning
confidence: 99%
“…Indeed, the two main current techniques used in calculating scattering amplitudes in SYM N = 4 are BCFW recursion and Wilson loop diagrams, both of which make use of the combinatorial machinery of positroids [8]. In particular, one finds that the Le diagrams are crucial for understanding the geometry underlying the Wilson loop diagrams [2]. In a forthcoming paper, we study the combinatorics of the positroids associated to Wilson loop diagrams, and show that the natural objects to use in this setting are the Grassmann necklaces.…”
Section: Introductionmentioning
confidence: 99%
“…Introduced in [Pos06], positroids have proven to be a combinatorially exciting family of matroids. Positroids have rich connections to total positivity [KW11], cluster algebras [PS14], and physics [AF18]. There are several ways to describe positroids combinatorially [Oh11] either via Grassmann necklaces, decorated permutations, Le-diagrams, among other combinatorial objects as stated in [Pos06].…”
Section: Introductionmentioning
confidence: 99%